Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi dan Sosialisasi SAK EMKM terhadap Penyusunan Laporan Keuangan UMKM - Gotami Soemaryo, Twella Marchi; Andi Aditya Hardinto (UNIVERSITAS KALBIS, 2025)
This study examines the impact of education level, accounting comprehension, and SAK EMKM socialization on MSMEs’ financial report preparation in North Cikarang. Data from 104 MSME actors were collected via purposive sampling and analyzed using multiple linear regression with STATA 16. The results show that accounting comprehension and SAK EMKM socialization have a significant positive effect, while education level does not. These findings highlight the need for practical training and SAK EMKM dissemination to enhance MSMEs’ financial reporting transparency and accountability.